2019
DOI: 10.25083/rbl/24.3/522.530
|View full text |Cite
|
Sign up to set email alerts
|

Bread making potential assessment of wheatoat composite flours

Abstract: In the recent years, evidence has been accumulated about the beneficial effects on consumers' health of oat in daily diets, respectively: maintaining blood cholesterol, lowering postprandial glucose, cardiovascular risk reduction, reducing oxidative stress and so on. The increase of oat content in bakery products, such as bread was generally associated with a decrease in volume and a worsening of sensorial characteristics, features that are guiding the consumer's decision to buy a particular product. Researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Numerous studies have confirmed that the addition of bran to wheat flour positively influences the properties of the dough and the bread quality (Cai et al., 2014; Curti et al., 2013). Also, the addition of oat products to wheat flour resulted in a significant increase in the water absorption, dough development time, and mixing tolerance of the obtained dough (Tamba‐Berehoiu et al., 2019). The changes noted in the properties of the quality of both triticale dough and bread were also noted after adding fiber‐rich oat concentrate to a baking blend containing triticale flour (Fraś et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have confirmed that the addition of bran to wheat flour positively influences the properties of the dough and the bread quality (Cai et al., 2014; Curti et al., 2013). Also, the addition of oat products to wheat flour resulted in a significant increase in the water absorption, dough development time, and mixing tolerance of the obtained dough (Tamba‐Berehoiu et al., 2019). The changes noted in the properties of the quality of both triticale dough and bread were also noted after adding fiber‐rich oat concentrate to a baking blend containing triticale flour (Fraś et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of triticale bran for triticale bread baking can improve the nutritional value of the obtained bread. It can also be assumed that, similarly to the studies on changes in the properties of wheat dough with added bran (Fraś et al, 2018;Tamba-Berehoiu et al, 2019), the addition of the triticale bran to triticale dough may also lead to changes in its rheological characteristics. The diversity of bread quality and its chemical composition is taken into account.…”
mentioning
confidence: 99%
“…Oats are a great source of protein and have been shown to possess several health benefits, including the maintenance of blood glucose levels and the reduction of oxidative stress [ 4 ]. Oat flour is often used in baby foods and ready-to-eat breakfast cereals [ 3 ], and trials are also being conducted for its use in bread production [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Variety (or hybrid), as a means of agricultural production, is one of the most important elements of scientific and technological progress in agriculture, since it ensures the production of high-quality products in necessary amount. The creation of new varieties is the most effective means of obtaining high yields at minimal cost [1,6,7,9].…”
Section: Introductionmentioning
confidence: 99%